The tobacco chloroplast YCF4 gene is essential for transcriptional gene regulation and plants photoautotrophic growth - Khan, Muhammad Sarwar; Riaz, Rimsha; Majid, Muhammad; Mehmood, Kashif; Mustafa, Ghulam; Joyia, Faiz Ahmad (Frontiers in Plant Science, 2022)
A tobacco chloroplast hypothetical open reading frame 4 (ycf4) has been reported as a non-essential assembly factor for photosynthesis based on an incomplete knockout of YCF4, just 93 of 185 amino acids from the N-terminus were knocked out. On the other hand, we removed the complete sequence of ycf4 from tobacco chloroplasts and observed that Δycf4 plants were unable to survive photoautotrophically as their growth was hampered in the absence of an external carbon supply, clearly showing that the YCF4 is essential for photosynthesis. Initially, the aadA gene was introduced into the tobacco plastome replacing the complete ycf4 gene through homologous recombination events. The replacement of ycf4 with aadA was confirmed by PCR and Southern blot analysis in Δycf4 plants. Homoplasmic Δycf4 plants had a light green phenotype, and the leaves became pale yellow as the plants grew older. The structure of chloroplasts of Δycf4 mutants of light green phenotype was studied using a transmission electron microscope (TEM), and the micrographs demonstrated structural anomalies in the chloroplasts; including shape, size, and grana staking compared to the untransformed wild-type plants. Further, transcriptome analysis revealed that the expression of PSI, PSII, and ribosomal genes remained unchanged in ∆ycf4 plants. On the other hand, transcriptome levels of rbcL, LHC, and ATP Synthase (atpB and atpL) decreased, indicating that the YCF4 has the function(s) in addition to assembling the photosynthetic complex. This was confirmed by in-silico protein-protein interactions of full-length YCF4 as well as 93 and 91 of 185 amino acids from N- and C-termini of the full-length protein, which revealed that the C-terminus (91 aa) of YCF4 is important in interacting with other chloroplast proteins. These findings provide genetic support for the plastid ycf4 gene's critical role in regulating the plastid gene expression and assembling the photosynthetic complex.